Effect of Moringa oleifera seed extract on antimicrobial activity and in vitro fertilization ability of cryopreserved ram semen - Guedea-Betancourt, Jose Julian; Quezada Casasola, Andres; Núñez-Gastélum, José Alberto; Orozco-Lucero, Ernesto; Escarcega Avila, Angelica Maria; Carrera Chavez, Jose Maria; Soler-Vals, Ana Josefa (2022)
Cryopreservation has adverse effects on the post-thaw sperm quality due to oxidative stress and the presence of bacteria. To minimize such effects, plant extracts have been included in the composition of the semen diluents. The objective of the present study was to evaluate the antimicrobial and antioxidant effects of Moringa oleifera seed extract (MOSE) on cryopreserved ram semen, as well as its impact on in vitro fertilization. Semen from six hair rams was treated with five treatments before cryopreservation: Control (without any antibiotic), Standard (conventional antibiotic), 1.0, 10.0, and 50.0 mg/ml of MOSE. Post-thawing sperm characteristics were evaluated by the computer-assisted semen analysis. Antimicrobial activity was assessed by counting colony-forming units (CFU) and the antioxidant capacity by the ferric reducing antioxidant power method. A heterologous in vitro fertilization technique was implemented to measure the fertilization rate. Progressive and rapid motility, membrane and acrosome integrity, and active mitochondria were higher (p < .05) in the 10.0 mg/ml treatment compared with Standard after thawing. All M. oleifera treatments showed inhibition of CFU. The antioxidant capacity of M. oleifera seed extract was higher in the 10.0 and 50.0 mg/ml treatments. Fertilization rate (cleavage percentage) was higher (p < .05) in the 10.0 mg/ml (82.9 ± 10.0) and Control (82.5 ± 9.9) treatments compared with Standard (73.7 ± 9.1). The addition of 10.0 mg/ml of MOSE to ram semen inhibits the development of microorganisms and improves sperm characteristics and the in vitro fertility of the semen.